(3GdfNHI aj eTJHg GdfSHIs - (3ESeGYjd Hf gHI Gddg Hf SYjO YeGO GdOjf, CHh GdeLO Hf HGWjT,J (B655 (3g` s
(3ChdgG (B:s
(3GdMeO ddg JYGdi MeOkG eTahYkG HKfGjg hHYO aEf Gddg JYGdi deG jSQ di GfgG eG cfJ TQYJ ai LeY ef cJGH eTJHg GdGfJSGH s
(3BNQgG (B:s
(3Gdjefi hGdjefi hCeG GdKGfi agh CHh RQYI eMeO Hf GHQGgje GdESJQGHGPi , fRd Gdjef hgh GdUbY GdeYQha afSH Zdjg hNdb cKjQ ShGg s
(3GdfSNI HgG MhGTs
(3HChdgG JQLeI ddeUfa HNW GdYdGeI YHO GdbGOQ Hf ecJhe GdbjS J (B749s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B328s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdJGQjNs